2012
DOI: 10.1007/s13280-012-0257-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change, Land Use Conflicts, Predation and Ecological Degradation as Challenges for Reindeer Husbandry in Northern Europe: What do We Really Know After Half a Century of Research?

Abstract: Reindeer grazing has been entitled as ecological keystone in arctic-alpine landscapes. In addition, reindeer husbandry is tightly connected to the identity of the indigenous Sámi people in northern Europe. Nowadays, reindeer husbandry is challenged in several ways, of which pasture degradation, climate change, conflicting land uses and predation are the most important. Research on reindeer-related topics has been conducted for more than half a century and this review illuminates whether or not research is capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 83 publications
3
81
0
Order By: Relevance
“…The reindeer (Rangifer tarandus tarandus) are herded in a pastoral system, where the animals move freely in the landscape during most of the year, often making extensive migrations between seasonal ranges to make use of the natural forage resources. One of the major threats to current Sámi reindeer husbandry is habitat loss due to direct or indirect impacts from competing land use (Danell 2005;Pape and Loeffler 2012). Numerous studies have documented large-scale effects on free-ranging reindeer from industrial development, resorts, roads, power lines and forestry operations, especially during late winter and the calving season (for review see Skarin and Å hman 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reindeer (Rangifer tarandus tarandus) are herded in a pastoral system, where the animals move freely in the landscape during most of the year, often making extensive migrations between seasonal ranges to make use of the natural forage resources. One of the major threats to current Sámi reindeer husbandry is habitat loss due to direct or indirect impacts from competing land use (Danell 2005;Pape and Loeffler 2012). Numerous studies have documented large-scale effects on free-ranging reindeer from industrial development, resorts, roads, power lines and forestry operations, especially during late winter and the calving season (for review see Skarin and Å hman 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of migration routes as a result of human activities and infrastructure has been observed for decades amongst reindeer herders (Klein 1971;Vistnes and Nellemann 2001;Ö ssbo and Lantto 2011;Pape and Loeffler 2012), however it has not previously been quantified scientifically with respect to free-ranging reindeer. The effects of reindeer on additional development in already fragmented landscapes are important to understand in order to address fully the impacts of progressive development (Nellemann et al 2003;Joly et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The reindeer (Rangifer tarandus tarandus) are herded in a pastoral system, where the animals move freely in the landscape during most of the year. One of the major threats for contemporary Sámi reindeer husbandry is habitat loss due to direct or indirect impact from competing land use (Danell 2005;Pape and Loeffler 2012). The UN Environment Programme and European Union have concluded that nearly one-third of the current traditional Sámi reindeer husbandry ranges in Northern Europe are severely affected by or partly inaccessible for reindeer herding due to the presence of infrastructure, industrial development or other human activity (UNEP 2001;.…”
Section: Introductionmentioning
confidence: 99%
“…This is a fairly novel concern: as late as the 1960s a key textbook on reindeer management did not discuss 'excessive' reindeer as an environmental problem (Skjenneberg 1965), but with the increased focus on environmental issues in the 1970s and 1980s terms such as 'overgrazing' (overbeiting) moved to the fore in Scandinavian research on reindeer management (Pape & Löffler 2012). Along with this increased attention, the matter of excessive reindeer was also progressively configured as a technical problem, to be 'solved' through managerial interventions (Reinert 2012).…”
Section: History Of a Perceived Ecological Crisismentioning
confidence: 99%